1986
DOI: 10.1210/jcem-63-2-323
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Pattern of Melatonin and Its Positive Relationship with Progesterone in Women

Abstract: To investigate the possible role of melatonin in the regulation of the human menstrual cycle, the circadian pattern of melatonin was determined in the follicular and luteal phases of 10 normal women. Four-hourly sampling was used to derive a melatonin index which described the total exposure to melatonin for 24 h. This sampling procedure adequately represented the circadian melatonin output and demonstrated that pulses of melatonin secretion, inconsistent with a measured half-life of 47 min, did not exist. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 23 publications
3
66
1
3
Order By: Relevance
“…There are several studies which observed an increase of the human serum melatonin level in the luteal phase compared to the follicular phase during the menstrual cycle (Arendt, 1978;Webley and Leidenberger, 1986). Opposite to this, Ito et al (1995) and Kivela et al (1988) reported no significant effect of the menstrual cycle on plasma or serum melatonin levels, but Kivela et al (1988) also found that the mean nighttime serum melatonin levels were significantly higher in winter than in summer during the follicular phase.…”
Section: Discussionmentioning
confidence: 96%
“…There are several studies which observed an increase of the human serum melatonin level in the luteal phase compared to the follicular phase during the menstrual cycle (Arendt, 1978;Webley and Leidenberger, 1986). Opposite to this, Ito et al (1995) and Kivela et al (1988) reported no significant effect of the menstrual cycle on plasma or serum melatonin levels, but Kivela et al (1988) also found that the mean nighttime serum melatonin levels were significantly higher in winter than in summer during the follicular phase.…”
Section: Discussionmentioning
confidence: 96%
“…In cycling women, Webley and Leidenberger 23 found that increased P 4 during the luteal vs. follicular menstrual phase was associated with significantly increased melatonin levels; furthermore, in women taking three-phase oral contraceptives, increased P 4 dosage also was associated with elevated total 24-hour melatonin exposure. Increased melatonin secretion in association with oral contraceptive use has been reported elsewhere.…”
Section: Melatonin Quantity Measuresmentioning
confidence: 99%
“…Mean serum ethinyloestradiol levels following 30 mg administration were reported to be about 0.5 nM [53], which is much lower than the concentration that caused impairment in the metabolism of melatonin (1 M) in the current study so that at clinically relevant concentrations (< 10 nM) it is unlikely to impair the sulphate conjugation of exogenous melatonin. However, the much lower endogenous levels of melatonin may be impaired by 17α-ethinyloestradiol and such a mechanism may explain to some extent why melatonin levels during the night are higher in females taking oral contraceptives [54][55][56]. Since 17-ethinyloestradiol appeared to decrease the sulphate conjugation of 6-hydroxymelatonin, it would be advisable in studies assessing melatonin treatment to exclude volunteers that use oral contraceptives as it could influence their melatonin profiles.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%